Conocimientos tributarios y la informalidad en comerciantes de pescado fresco del mercado de Belén, Iquitos – año 2021 - Huayambi Chanchari, Ray Dandy (2023)
The present research work entitled "Relationship between the level of Tax Knowledge and Informality in Fresh Fish Merchants of the Belén Market, Iquitos - Year 2021" was carried out with the objective of determining what is the level of Tax Knowledge and its relationship with the attitude towards Informality in fresh fish merchants of the Belén Market, Iquitos - Year 2021, for which a descriptive and Correlational investigation was chosen, of a non-experimental design, where 15 fish vendors were taken as the study population. fresh fish from the Belén market who voluntarily decided to participate in this research work, to whom the survey technique was applied and the questionnaire as an instrument; According to the analysis of the results, it was determined that 72.5% of the fresh fish vendors of the Belén Market, Iquitos - Year - 2021 have a low level of tax knowledge, 27.5% have a medium level of tax knowledge and in terms of attitude towards informality, 82.2% of the fresh fish merchants of the Belén Market, Iquitos, year 2021 have a high level of positive attitude towards informality, and 17.8% have a low level of negative attitude towards Informality, it is concluded that the fresh fish merchants of the Belén Iquitos market - year 2021, have an indirect relationship between tax knowledge and the attitude towards informality.